Pemilu Parlemen ke-7 dan Prospek Gerakan Reformasi di Iran - Kartini, Indriana (Jurnal Penelitian Politik, 2004)
Reformism is the belief that gradual changes in a society can change its fundamental structures. This belief also has a great influence in the mind o f many Iranian people whose struggle for a change, including the mullahs and politicians that led them changed their face from radical to moderat e in a tremendous movement called â€œthe reform movementâ€. This movement has crystallized since Mohammad Khatami has been elected as the President o fthe Islamic Republic o f Iran in 1997 and this event became the first victory o fth e reform movement. The second victory was obtained by the reformist or the leftist in the 6th parliamentary (Majlis) election in 2000, which strengthened the reform movement. But the scene o f victory now has been turning back into the hands o f the conservative or the rightist. In the 7lh parliamentary election, the rightist who has changed to pragmatic face won the majority o f the Majlis seat. This political change happened because of the disillusioned of Iranian people has frustrated by the leftist due to their failure to bring into reality their reform promises. Therefore, solving the peopleâ€™s problem will be the big task o f the seventh Majlis, regardless o f which faction forms the majority.